Directional Construction of Vertical Nitrogen‐Doped 1T‐2H MoSe2/Graphene Shell/Core Nanoflake Arrays for Efficient Hydrogen Evolution Reaction. Issue 21 (3rd April 2017) - Deng, Shengjue; Zhong, Yu; Zeng, Yinxiang; Wang, Yadong; Yao, Zhujun; Yang, Fan; Lin, Shiwei; Wang, Xiuli; Lu, Xihong; Xia, Xinhui; Tu, Jiangping
Abstract : The low utilization of active sites and sluggish reaction kinetics of MoSe2 severely impede its commercial application as electrocatalyst for hydrogen evolution reaction (HER). To address these two issues, the first example of introducing 1T MoSe2 and N dopant into vertical 2H MoSe2 /graphene shell/core nanoflake arrays that remarkably boost their HER activity is herein described. By means of the improved conductivity, rich catalytic active sites and highly accessible surface area as a result of the introduction of 1T MoSe2 and N doping as well as the unique structural features, the N‐doped 1T‐2H MoSe2 /graphene (N‐MoSe2 /VG) shell/core nanoflake arrays show substantially enhanced HER activity. Remarkably, the N‐MoSe2 /VG nanoflakes exhibit a relatively low onset potential of 45 mV and overpotential of 98 mV (vs RHE) at 10 mA cm −2 with excellent long‐term stability (no decay after 20 000 cycles), outperforming most of the recently reported Mo‐based electrocatalysts. The success of improving the electrochemical performance via the introduction of 1T phase and N dopant offers new opportunities in the development of high‐performance MoSe2 ‐based electrodes for other energy‐related applications. Abstract : A new powerful strategy to remarkably boost the electrocatalytic activity of MoSe2 /graphene nanoflakes by introducing 1T MoSe2 and a N dopant simultaneously is demonstrated. These N‐doped MoSe2 /graphene nanoflakes show outstanding hydrogen evolution reaction performance, with a small overpotential of 98 mV, a low Tafel slope of around 49 mV dec −1, and an excellent long‐term durability.